Shakespeare's spy - Blackwood, Gary (New York : Puffin Books, 2005)
The winter of 1602 brings many changes for Widge, a young apprentice at London's Globe Theatre, as he becomes infatuated with Shakespeare's daughter Judith, attempts to write a play, learns more about his past, endangers himself to help a friend, acquires a new identity, and finds a new purpose in life.
Keywords: Great Britain -- History -- Elizabeth, 1558-1603 -- Fiction; Historical fiction